Home Literacy Activities and Children’s Reading Skills, Independent Reading, and Interest in Literacy Activities From Kindergarten to Grade 2 - Silinskas, Gintautas; Sénéchal, Monique; Torppa, Minna; Lerkkanen, Marja-Kristiina (Frontiers in Psychology, 2020)
According to the Home Literacy Model (Sénéchal & LeFevre, 2002, 2014), young children can be exposed to two distinct types of literacy activities at home. First, meaning-related literacy activities are those where print is present but is not the focus of the parent–child interaction, for example, when parents read storybooks to their children. In contrast, code-related literacy activities focus on the print, for example, activities such as when parents teach their children the names and sounds of letters or to read words. The present study was conducted to expand the Home Literacy Model by examining its relation with children’s engagement in literacy activities at home and at school as Finnish children transitioned from kindergarten to Grades 1 and 2. Two facets of children’s engagement were examined, namely, children’s independent reading at home and their interest in literacy activities. Finnish children (N = 378) were tested and interviewed at the ends of kindergarten, Grade 1, and Grade 2. Mothers completed questionnaires on their home literacy activities at each test time, and they reported the frequency with which their children read independently twice when children were in grade school. Tested was a longitudinal model of the hypothesized relations among maternal home literacy activities (shared reading and teaching of reading), children’s reading skills, independent reading, and their interest in literacy activities/tasks as children progressed from kindergarten to Grade 2. Stringent path analyses that included all auto-regressors were conducted. Findings for a revised model that excluded child interest extended previous research in four ways. First, the frequency of shared reading and teaching of reading at home predicted the frequency of children’s independent reading one year later. Second, children with stronger early literacy skills in kindergarten read independently more frequently once they were in Grade 1. Third, parents adapted, from kindergarten to Grade 1, their teaching behaviors to their children’s progress in reading, whereas shared reading decreased over time. Fourth, children’s own reports of interest in literacy activities were mostly not linked to other variables. Taken together, these results add another layer to the Home Literacy Model.